2016
DOI: 10.1002/cssc.201600710
|View full text |Cite
|
Sign up to set email alerts
|

Ni Nanoparticles Supported on Cage‐Type Mesoporous Silica for CO2 Hydrogenation with High CH4 Selectivity

Abstract: Ni nanoparticles (around 4 nm diameter) were successfully supported on cage-type mesoporous silica SBA-16 (denoted as Ni@SBA-16) via wet impregnation at pH 9, followed by the calcination-reduction process. The Ni@SBA-16 catalyst with a very high Ni loading amount (22.9 wt %) exhibited exceptionally high CH4 selectivity for CO2 hydrogenation. At a nearly identical loading amount, the Ni@SBA-16 catalysts with smaller particle size of Ni NPs surprisingly exhibited a higher catalytic activity of CO2 hydrogenation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Bacariza et al [28] fabricated an Ni-based MCM-41 catalyst, which presented high CO 2 conversion. Moreover, as reported by Lu et al [29], the Ni-grafted SBA-15 catalyst was suitable for CO 2 methanation because its cage-type mesoporous structure facilitated the formation of small Ni nanoparticles, resulting in an improvement in the catalytic performance [30]. Although partial progress has been made, it is still hard to suppress the coke formation and sintering of Ni nanoparticles while achieving a high catalytic activity.…”
Section: Introductionmentioning
confidence: 96%
“…Bacariza et al [28] fabricated an Ni-based MCM-41 catalyst, which presented high CO 2 conversion. Moreover, as reported by Lu et al [29], the Ni-grafted SBA-15 catalyst was suitable for CO 2 methanation because its cage-type mesoporous structure facilitated the formation of small Ni nanoparticles, resulting in an improvement in the catalytic performance [30]. Although partial progress has been made, it is still hard to suppress the coke formation and sintering of Ni nanoparticles while achieving a high catalytic activity.…”
Section: Introductionmentioning
confidence: 96%
“…As the methanation reaction is highly exothermic, great effort has been devoted to anchoring or immobilizing Ni nanoparticles onto support materials in attempts to alleviate high-temperature sintering 69 . Because of such efforts, spatial confinement has emerged as an effective and unique way to limit the growth of Ni nanoparticles 10,11 . Chen et al 11 pointed out that a “cage” of mesoporous SBA-16 could confine small Ni nanoparticles, thereby contributing to their high activity in the reverse water–gas shift reaction (i.e., hydrogenation of CO 2 to CO).…”
Section: Introductionmentioning
confidence: 99%
“…[170] The nanoparticles with large surface area-to-volume ratio often suffer from the oxidation or aggregation of particles, resulting in a limited catalytic performance with uncontrollable and undesirable effects. [171] For instance, Baturina et al demonstrated that under similar experimental conditions, 12 and 19 nm Cu nanoparticles exhibit similar FEs to H 2 , C 2 H 4 , CO, and CH 4 , in which the product distribution is dominated by C 2 H 4 over CH 4 . The similar performance of 12 and 19 nm Cu nanoparticles is attribute to the higher agglomeration of Cu nanoparticles, which leads to a different surface structure from that of ideal cubo-octahedral nanoparticles at a given size.…”
Section: Suppressing the Deactivation Of Catalystsmentioning
confidence: 97%
“…The nanoparticles with large surface area‐to‐volume ratio often suffer from the oxidation or aggregation of particles, resulting in a limited catalytic performance with uncontrollable and undesirable effects. [ 171 ] For instance, Baturina et al. demonstrated that under similar experimental conditions, 12 and 19 nm Cu nanoparticles exhibit similar FEs to H 2 , C 2 H 4 , CO, and CH 4 , in which the product distribution is dominated by C 2 H 4 over CH 4 .…”
Section: Suppressing the Deactivation Of Catalystsmentioning
confidence: 99%